Método multirresíduo para monitoramento de contaminação ambiental de pesticidas na região de Bauru (SP) usando mel como bio-indicador - Rissato, Sandra Regina [UNESP]; Galhiane, Mario Sergio [UNESP]; Knoll, Fátima do Rosário Naschenveng [UNESP]; Andrade, Rita Mickaela Barros de; Almeida, Marcos Vinícius de (Sociedade Brasileira de Química, 2006)
The presence of residues of the major groups of pesticides (organohalogen, organophosphorous, pyrethroids and organonitrogen) in representative samples of honey produced in Bauru (state of São Paulo, Brazil) was investigated from 1999 through2004. A multiresidue method was applied to honey samples to determine 48 pesticides with recoveries ranging from 76 to 95%. The limits of detection found were lower than 10 µg/kg for GC-MS-SIM. The results indicated that most pesticides found in the samples belonged to the organohalogen and organonitrogen groups. Residues of malathion were detected in almost all of the samples in high concentration.
Multiresidue method for monitoring environmental contamination by pesticides in the Bauru region (SP) using honey as bioindicator
Keywords: multiresidue pesticide; honey; environmental contamination